Impact of HRM on Handloom as an unorganized sector (A study with reference to Handloom weavers in Krishna District, A.P) - Rao, Dr. P. Rama Chandra (IJRDO - Journal of Business Management, 2019)
Handloom weaving activity is much popular and decentralized, traditional and skill oriented activity in India. It is spread every nook and corner of the country and occupied everywhere both in rural and urban areas. After agriculture, the handloom industry provides significant proportion of livelihoods to majority of its people. India has great heritage in handloom sector. The scope of employment is heavy; nearly 43.31 lakh people are engaged directly or indirectly by this activity.The present study is based on the primary data collected from handloom weavers in Krishna district, where majority of handloom weavers are located. The human resource generation is stagnated in handloom sector as well as the choosing this occupation also by heredity or profession by parents only. This study aims at to explore the Human Resources Management practices in handloom weaving activity as well as to suggest appropriate measures to implement the HRM practices.